IMPOLITENESS STRATEGIES IN HATE COMMENTS ON NOAH SCHNAPP’S INSTAGRAM POSTS - Kaulika, Adinya Kalya; Mansyur, Agus Salim; Wardoyo, Cipto (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2024)
This research aims to investigate the impoliteness strategies in hate comments on Noah Schnapp’s Instagram posts and explain the function of impoliteness strategies manifested by netizens in Noah Schnapp’s Instagram posts. The controversy that arose after Schnapp openly supported Zionism triggered a flood of hate comments from netizens. The research used Jonathan Culpeper’s theory of impoliteness (1996) to identify five types of impoliteness strategies: negative impoliteness, bald on record impoliteness, positive impoliteness, sarcasm or mock politeness, and withhold politeness. The data were collected from netizens' utterances on Noah Schnapp's Instagram posts and analyzed using a descriptive qualitative method. As a result, out of 30 data analyzed, the negative impoliteness strategy was the most dominant (15 data), followed by bald on record (7 data), sarcasm or mock politeness (4 data), and positive impoliteness (4 data), while withhold politeness was not found. In terms of function, most of the comments reflect affective functions (16 data), which show emotional outbursts such as anger or disappointment, followed by coercive functions (9 data), and entertainment functions (5 data).